3.3 S1=1·2·3/3 =2 werno S2= 2·3·4 /3 = 8 werno S3= 3.4.5/3 = 20 werno предположим что для Sn верно, докажем что S(n+1) = Sn + (n+1)(n+2) n(n+1)(n+2)/3 + (n+1)(n+2) = (n+1)(n+2)·[n/3+1] = (n+1)(n+2)·(n+3)/3=S(n+1) доказано4.3 2x -10y +4i -xi+5yi +2 -6xi +2 = -3i+6 (7 -7x +5y)i = 2-2x +10y [7(1-x) +5y]i =2(1-x) + 10y ⇒ x=1 ; y=0 7x -5y =7 : 2x - 10y =2 14x -10y =14 ⇒ 12x=12 ⇒ x=1 7-5y= 7 ⇒ y=0 1.3 C= [-3;3] ; D = (-3;0]U[2;3) C = [-3;0]u(0;2)U[2;3] ⇒ C∩D = (-3;0] U [2;3) C U D = [-3;3] C\D = 3U(0;2)U3 D\C = ∅ 2.3 f(x)= - |x| D(f) = (-∞; +∞)| E(f) = (-∞; 0]